Safety and Efficacy of a Pentavalent Human–Bovine (WC3) Reassortant Rotavirus Vaccine - Vesikari, Timo; Matson, David O; Dennehy, Penelope; Van Damme, Pierre; Santosham, Mathuram; Rodriguez, Zoe; Dallas, Michael J; Heyse, Joseph F; Goveia, Michelle G; Black, Steven B; Shinefield, Henry R; Christie, Celia D.C; et al. (The New England journal of medicine, 2006)
In this randomized trial, the clinical efficacy of an oral, live pentavalent human–bovine reassortant vaccine was estimated to be 98.0 percent against severe gastroenteritis due to rotavirus. In the safety study, which included 68,038 infants, the rates of intussusception were similar in the vaccine and placebo groups (relative risk, 0.8; 95 percent confidence interval, 0.3 to 1.8). In this randomized trial, the clinical efficacy of an oral, live pentavalent human–bovine reassortant vaccine was estimated to be 98.0 percent against severe gastroenteritis due to rotavirus. Rotavirus is the leading cause of hospitalization and death from acute gastroenteritis among infants and young children worldwide. More than 2 million hospitalizations and nearly half a million deaths are attributed to this infection annually. 1 , 2 The strategy of preventing rotavirus through vaccination derives from studies demonstrating that wild-type rotavirus infection induces immunity against subsequent rotavirus gastroenteritis. 3 – 6 Primary rotavirus infection provides substantial protection against gastroenteritis caused by the same serotype and against severe disease regardless of serotype. The four most prevalent serotypes, which account for more than 80 percent of cases of human rotavirus disease worldwide, are G1P[8], G2P[4], . . .